Pengaruh Marketing Mix Syariah (7P) terhadap Minat Beli Produk Jasa (Studi Kasus pada PT. Nurul Muflihun Al-Barokah Cabang Serang) - Muharromah, Zahratul; Syihabudin; Najmudin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to analyze the influence of the Sharia Marketing Mix (7P) on the purchase interest of service products at PT. Nurul Muflihun Al-Barokah Serang Branch. The Sharia Marketing Mix consists of seven elements: product, price, place, promotion, people, process, and physical evidence. This research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to consumers of PT. Nurul Muflihun Al-Barokah. Direct observations of potential pilgrims and interviews with PT. Nurul Muflihun Al-Barokah staff and Umrah pilgrims were also conducted. The results of multiple linear regression analysis show that the variables of product, price, promotion, people, process, and physical evidence significantly influence consumer purchase interest, while the variable of place does not show significant influence. These findings indicate the importance of focusing on product, price, promotion, people, process, and physical evidence in marketing strategies to increase consumer purchase interest. This research is expected to contribute to the development of more effective marketing strategies in the Sharia-based service industry. Keyword: Purchase Interest, Service Pruducts, Sharia Marketing Mix